DETERMINANTS OF QRIS CONTINUANCE INTENTION AMONG GEN Z INDONESIA WITH SYSTEM QUALITY AS MODERATION - Amalia, Annisa; Nurabiah, Nurabiah (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.07.TAHUN.2025, 2025)
Generation Z in Indonesia shows a strong interest in cashless digital financial products, such as e-wallets, which reflects their readiness for digital transactions through QRIS. Understanding the factors that influence continued usage is crucial for encouraging QRIS adoption and supporting the growth of the digital ecosystem. This study explores the roles of ease of use, living cost management, and conformity in influencing the intention to use QRIS, with system quality as a moderating variable. The research involved a sample of 1.116 Generation Z individuals and applied a quantitative approach using SmartPLS 4. The results show that ease of use, living cost management, and conformity significantly affect the intention to continue using QRIS. Among these factors, conformity, defined as the desire to follow prevailing trends, has the most decisive influence. System quality enhances the effect of ease of use but weakens the impact of conformity and has no significant effect on living cost management. Interestingly, the weakening of conformity's effect by system quality highlights the dominance of intrinsic motivation over social pressure. This study highlights the importance of balancing technical innovation with psychological and social factors to strengthen QRIS adoption.